2014
DOI: 10.2337/dc13-0626
|View full text |Cite
|
Sign up to set email alerts
|

B-Lymphocyte Depletion With Rituximab and β-Cell Function: Two-Year Results

Abstract: OBJECTIVEWe previously reported that selective depletion of B-lymphocytes with rituximab, an anti-CD20 monoclonal antibody, slowed decline of β-cell function in recent-onset type 1 diabetes mellitus (T1DM) at 1 year. Subjects were followed further to determine whether there was persistence of effect.RESEARCH DESIGN AND METHODSEighty-seven subjects (aged 8–40 years) were randomly assigned to, and 81 received, infusions of rituximab or placebo on days 1, 8, 15, and 22. The primary outcome—baseline-adjusted mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
176
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(195 citation statements)
references
References 17 publications
5
176
0
3
Order By: Relevance
“…Subjects received four weekly injections of rituximab and were then monitored for 12 months (Pescovitz et al 2009(Pescovitz et al , 2014. Adverse events of limited severity are mostly seen after the first infusion of Ab, and no increase in infections is detected in rituximab-treated subjects likely reflecting preservation of memory B cells.…”
Section: B Cell Depletionmentioning
confidence: 99%
“…Subjects received four weekly injections of rituximab and were then monitored for 12 months (Pescovitz et al 2009(Pescovitz et al , 2014. Adverse events of limited severity are mostly seen after the first infusion of Ab, and no increase in infections is detected in rituximab-treated subjects likely reflecting preservation of memory B cells.…”
Section: B Cell Depletionmentioning
confidence: 99%
“…Antibodies for CD24(30-F1), CD4(GK1.5), IgM(II/41) IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), BP1(6C3), CD19(eBio1D3), CD43(eBioR2/60), and CD23(B3B4) as well as efluor 450-labeled streptavidin were purchased from eBioscience (San Diego, CA). Dead cells were excluded using DAPI or aqua fluorescent reactive dye (Invitrogen, Carlsbad, CA).…”
Section: Flow Cytometry and Antibodiesmentioning
confidence: 99%
“…These studies indicate that B cells play an important role in early priming and expansion of autoimmune responses. However, therapies that target B cells, including blockade of B-cell receptor (BCR) signaling (9) and depletion of B cells by anti-CD20 or anti-CD22-cal, have yielded variable results (10)(11)(12)(13)(14)(15). On the other hand, targeting T cells by anti-CD3 was also found to have limited effect in new-onset diabetic patients (16).…”
mentioning
confidence: 99%
“…In patients with T1D, many immunologic strategies have been tested in phase II clinical trials; however, most of the results from these studies have been disappointing, with no single or combination treatment providing an unambiguous benefit in preserving β cell function. In a few studies, individuals have shown transient benefit (3)(4)(5)(6), while others have been without any observed benefit (7)(8)(9)(10). Still other immune interventions have ambiguous effects that do not meet their primary outcome measure, such as preservation of β cell function, but provide potential benefit based either on secondary outcome measures or mechanistic findings (11,12).…”
mentioning
confidence: 99%